Transnational Intellectual Property Strategies and Firms’ Knowledge Adoption: Evidence from China-U.S. Patent Dyads - HUANG, Kenneth Guang-Lih (Institutional Knowledge at Singapore Management University, 2012)
As firms increasingly conduct R&D in emerging markets, ‘transnational patenting’– patenting of the same invention across more than one country– is becoming a cornerstone of their intellectual property (IP) strategies. We investigate how patenting of a firm’s invention in an emerging economy (China) can shape its subsequent technological knowledge adoption by other firms in a developed economy (U.S.). Using 4,226 China-U.S. patent dyads covering 1,104 firms, our difference-in-differences estimates show that patent grant under a weak IP institution (China) increases the technology’s knowledge adoption under a strong IP institution (U.S.). Such signaling effect to mitigate information asymmetry is most salient for patents awarded to China-based firms, in computing and information sector, and to technologies developed in Chinese provinces with lower de facto IP institutional quality.